Social transcultural representations about the concept of university social responsibility. Issue 2 (1st February 2019) - Ayala-Rodríguez, Nelly; Barreto, Idaly; Rozas Ossandón, Germán; Castro, Alejandra; Moreno, Sebastián
ABSTRACT: The new paradigms of university social responsibility (USR) conceive students as key players who express their beliefs, attitudes and opinions both in the professional training process and in their willingness to serve the community in line with the agenda of USR. This research focuses on a comparative study of the social representations that students of two higher education institutions have on the concept of USR. From a qualitative methodological perspective, using focus groups and semi-structured interviews as the information collection technique, the narratives of 50 participants were analysed by codifying and prioritizing the categories in accordance with the assumptions of the central core theory for the study of social representations. The results show that the central core of the representation focuses on prosocial sense . The peripheral elements are associated with social awareness, mutual respect, co-responsibility, social projection, university identity, and comprehensive education and entrepreneurship, among others.